CXCL13, CXCL10 and CXCL8 as indicators of ocular and neurological involvement in patients with ocular syphilis: an observational descriptive study - Van der Merwe, Laurie Wiid (Stellenbosch : Stellenbosch University, 2023)
Thesis (MMed)--Stellenbosch University, 2022.